Assistance in the Submission of Halal Certification through the Self-Declare Scheme for Small Enterprises - Irfan Anshori; Uus M Husaini; Diyar Nurhidayati; Nesi Fidiyani (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Halal products hold significant religious and cultural importance for Muslims, ensuring adherence to Islamic law, ethical practices, sustainability, and consumer trust through certification, enhancing competitiveness and contributing to the development of the global halal industry. This community service activity aims to describe the mentoring process for halal certification via the self-declare scheme, starting from obtaining a business permit through the OSS (Online Single Submission) system to the submission of documents on the SiHalal platform. The activity employed a Participatory Action Research approach, involving 100 small business actors and 10 mentors in Susukan Village, using presentations and documentation as supporting media. The results indicate that the halal certification mentoring program is a close collaboration between halal facilitators and business actors, resulting in the successful acquisition of business identification numbers and halal certificates. The business permits were obtained through the OSS website, while halal certification was submitted through the SiHalal platform. The self-declare scheme is only applicable to businesses that do not process meat-based products, use packaging free from pornographic elements, and have product names that are free from ethnic, religious, racial, or inter-group issues. Certification submission requires the business owner's identity, business license number, and product photos with proper packaging. The halal certificate enhances consumer trust, expands distribution opportunities, and supports Indonesia's goal of becoming a global halal hub. In conclusion, the halal certification mentoring was well received, significantly improving the legal standing of business actors' products and expanding their market reach.